Abrem-se as cortinas do teatro do oprimido no movimento de alfabetização de jovens e adultos em Osasco - Santos, Francisca Maria dos (2014)
The object of this research is the contribution of the Theatre of the Oppressed through the intervention of exercises, games and drama for the acquisition of reading and writing literacy in a room of the Youth and Adult Literacy Movement (MOVA). The objectives were to identify if games used contribute to the acquisition of reading and writing; conceptually interpret its effectiveness to appoint new subsidies for action and intervention by mediation of games and exercises TO practiced as a teaching methodology. Is taken as references to Freire's concept of education and the assumptions TO Augusto Boal (1931-2009). An educator and sevens educandas a nucleus implanted in Osasco (SP) were research subjects. The first step was the observation of planning educator and then were embedded games and exercises of the Theatre of the Oppressed to give support to activities undertaken. Ten weekly meetings, each lasting three hours, with the teacher for planning and evaluation activity, and educandas for the realization of educational intervention with the games, exercises and role plays were performed. Whereas the "be" in view of liberating education Freire (1987), this study provided that the intervening group of women to experience through the theatrical language knowledge and recognition of the body as a fundamental process within the dimension acquisition of reading and writing. The survey results also showed that the games and drama exercises constitute themselves as a major participation and dialogue between peers path, expanding the recognition of self and establishing communication with another in a firm that subjective identity, articulating -a to its surroundings. It is a means of developing speech and exchange of life experiences. Thus, it might be experienced by a group of women who had little knowledge of writing and reading. Among the women in the group found that the development of body expression, extending the dialogical relationship, a fact that enabled the perception of self and other as a tool for understanding that collectively acquire great potential for finding solutions in situations and experienced problems.